Occurrence, management and outcomes of hip fractures in patients with Parkinson's disease. Issue 1 (29th June 2015) - Critchley, Rebecca J.; Khan, Sameer K.; Yarnall, Alison J.; Parker, Martyn J.; Deehan, David J.
Abstract : Introduction: Hip fractures can be debilitating, especially in patients with pre-existing Parkinson's disease; they have reportedly worse outcomes than non-Parkinson's disease patients. Sources of data: A computerized literature search on PubMed, Medline, Embase, and CINAHL, supplemented by a manual search of related publications. Areas of agreement: Parkinson's disease patients were found to have significantly lower bone mineral density; higher incidence of falls and hip fractures; delays to receiving their Parkinson's disease medication and surgery; higher risk of pneumonia, urinary infection, pressure sores, post-operative mortality; surgical complications and sequelae, including failed fixation, dislocation, longer hospital stay, re-operation; and increased risk of contralateral hip fracture. Areas of controversy: Regain of mobility and return to previous residential status have been variably reported. Growing points: All Parkinson's disease patients should be screened and considered for primary prevention treatment. On admission with hip fractures, attention should be paid to avoid delays to medication, ensuring safe anaesthetic and timely surgery, and post-operative chest physiotherapy and mobilization. Research: Research is needed in minimizing the bone-resorptive effects of anti-Parkinson's disease medication.